Virtuality: The New Meeting Space and Time Between Human Science and Technology - Noruega, Ana Patricia (2004)
In Western culture, this split has its origin in the Platonic idea of ​​the existence of two worlds: The world of ideas, that is, of the real, and the world of appearances or the world of what appears to us, which is this tangible and earthly world, material and degenerative, this world in motion (Noguera, 2003).